2006
DOI: 10.1007/s10562-006-0172-1
|View full text |Cite
|
Sign up to set email alerts
|

XPS evidence for molybdenum nitride formation in ZSM-5

Abstract: This communication presents XPS evidence for the formation of molybdenum nitride or oxynitride species in ZSM-5 when HZSM-5 loaded with MoO 3 is subjected to temperature programmed reaction with ammonia. We suggest that this chemistry provides a potential route to zeolite dispersed transition metal nitride catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
(23 reference statements)
2
22
0
Order By: Relevance
“…As shown elsewhere [25], the XPS spectrum of bulk MoO 3 in the Mo 3d region showed a single spin orbit doublet (Mo 3d 3/2 and Mo3d 5/2 with an intensity ratio of 2:3) with a Mo 3d 5/2 binding energy of 233.0 eV. Upon ammonolysis to produce c-Mo 2 N, it was found that there was a superposition of this doublet with a second doublet at lower binding energy (Mo3d 5/2 ca 229.8 eV).…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…As shown elsewhere [25], the XPS spectrum of bulk MoO 3 in the Mo 3d region showed a single spin orbit doublet (Mo 3d 3/2 and Mo3d 5/2 with an intensity ratio of 2:3) with a Mo 3d 5/2 binding energy of 233.0 eV. Upon ammonolysis to produce c-Mo 2 N, it was found that there was a superposition of this doublet with a second doublet at lower binding energy (Mo3d 5/2 ca 229.8 eV).…”
Section: Resultsmentioning
confidence: 54%
“…This latter point suggests that Mo is in an oxidation state lower than VI. It is also different from the passivating layer found on the bulk nitride [25]. Generally consistent trends were found in the Mo 2p region where, additionally, the N 1s feature was observed at *398.0 eV and the estimated N:Mo ratios for the freshly nitrided and etched samples were *1.0 and *0.5, respectively.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, the Mo/Si ratios determined by XPS in elucidating the possible dispersion of molybdenum nitride clusters within H-ZSM-5 from MoO 3 /H-ZSM-5 suggest redistribution of the Mo species upon nitridation [12,13]. In situ FTIR studies following thermal activation of MoO 3 / H-ZSM-5 evidence loss of OH features at 3733, 3613 and 3440 cm -1 corresponding to terminal OHs, bridging OHs and hydroxyl nests, respectively [13].…”
Section: Dehydroaromatisation Of Methanementioning
confidence: 99%
“…In recent years, new types of catalyst, such as transition metal nitrides and oxynitrides [11][12][13][14] have been studied for hydrotreatment [15][16][17], HDS [18][19][20][21][22][23] and HDN [24][25][26][27][28][29][30][31][32][33][34]. Molybdenum nitrides with a high surface area have been extensively developed by the temperature-programmed nitridation of MoO 3 with ammonia [35][36][37][38][39] or N 2 ? H 2 [40][41][42] under conditions applying low heating rates, small precursor particle sizes and high space velocities.…”
Section: Introductionmentioning
confidence: 99%